Why cellular communication during plant reproduction is particularly mediated by CRP signalling - Bircheneder, Susanne (Journal of experimental botany, 2016)
© The Author 2016. Published by Oxford University Press on behalf of the Society for Experimental Biology. All rights reserved. For permissions, please email: journals.permissionsoup.com.